Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0008-6363(00)00071-7
|View full text |Cite
|
Sign up to set email alerts
|

Unstable angina activates myocardial heat shock protein 72, endothelial nitric oxide synthase, and transcription factors NFκB and AP-1

Abstract: HSP72 and eNOS, which may be associated with cardioprotection in ischemic preconditioning, are increased in atrial tissue of patients with unstable angina. Activation of NFkappaB and AP-1, which regulate a battery of inflammatory genes, was found in hearts of unstable patients. NFkappaB activation may induce a myocardial proinflammatory state, possibly making the unstable myocardium more susceptible to the inflammation induced by open heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Pathological and autopsy studies have reported that rupture or erosion of multiple vulnerable plaques and subsequent formation of thrombus are the most important mechanisms leading to ACS, whereas SA closely correlates with the stability of an atherosclerotic plaque (Hong et al 2004). Consistent with our results, increased Hsp70 levels have been detected in heart biopsies from patients with unstable, as compared with stable angina (Valen et al 2000). It is possible that soluble Hsp70 release into the circulation is higher in the sudden fissure or rupture of unstable plaque, and acute events, following AMI for example, rather than in stable plaque.…”
Section: Discussionsupporting
confidence: 91%
“…Pathological and autopsy studies have reported that rupture or erosion of multiple vulnerable plaques and subsequent formation of thrombus are the most important mechanisms leading to ACS, whereas SA closely correlates with the stability of an atherosclerotic plaque (Hong et al 2004). Consistent with our results, increased Hsp70 levels have been detected in heart biopsies from patients with unstable, as compared with stable angina (Valen et al 2000). It is possible that soluble Hsp70 release into the circulation is higher in the sudden fissure or rupture of unstable plaque, and acute events, following AMI for example, rather than in stable plaque.…”
Section: Discussionsupporting
confidence: 91%
“…19 Unstable angina activates cardiac heat shock protein 72, eNOS, and the transcription factor NFkB in patients with recent symptoms. 20 We speculate that, from an adaptive point of view, it appears sensible for an organism subjected to an acute ischemic event or inflammation of another etiology to defend itself against a possible next event in the same or another organ through increasing endogenous protection. The present findings pinpoint that organ protection is generated by ischemia, rather than by ischemia and reperfusion, and may thus represent a key to the pathway of solving the preconditioning enigma.…”
Section: Discussionmentioning
confidence: 92%
“…[7][8][9] However, there are few reports on circulating HSPs in human diseases. [23][24][25] The early peak of inducible HSP70 in plasma after CABG as demonstrated in our study is striking.…”
Section: Discussionmentioning
confidence: 99%
“…7 Myocardial ischemia induces HSP70 as a stress response, 7 and HSP70 is increased in atrial tissue of patients with unstable angina. 8 Demidov and coworkers 9 found induction of HSP70 in myocardial cells in 40% of 33 patients undergoing CABG. Circulating inducible HSP70 after CABG has, to our knowledge, not been demonstrated previously.…”
mentioning
confidence: 99%